2013
DOI: 10.1371/journal.pone.0065810
|View full text |Cite
|
Sign up to set email alerts
|

Modified Lipoprotein-Derived Lipid Particles Accumulate in Human Stenotic Aortic Valves

Abstract: In aortic stenosis plasma lipoprotein-derived lipids accumulate in aortic valves. Here, we first compared the lipid compositions of stenotic aortic valves and atherosclerotic plaque cores. Both pathological tissues were found to be enriched in cholesteryl linoleate, a marker of extracellularly accumulated lipoproteins. In addition, a large proportion of the phospholipids were found to contain arachidonic acid, the common precursor of a number of proinflammatory lipid mediators. Next, we isolated and characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 68 publications
1
22
0
1
Order By: Relevance
“…Acquisition of direct evidence that eLDL is indeed present extracellularly became a pressing issue, and immunohistochemical localization appeared to us the method of choice. If we may assume that enzymatic degradation and fusion of lipid particles are essentially synonymous,10 our findings are in perfect accordance with the recently published electron micrographs of isolated extracellular lipid particles from aortic valves 26. Compared with the histological structure of adaptive intimal thickening of human arteries prone to atherosclerotic lesion development,27 the composition of the human aortic valve cusp with the fibrosa suffused with insudated lipoproteins is quite different.…”
Section: Discussionsupporting
confidence: 88%
“…Acquisition of direct evidence that eLDL is indeed present extracellularly became a pressing issue, and immunohistochemical localization appeared to us the method of choice. If we may assume that enzymatic degradation and fusion of lipid particles are essentially synonymous,10 our findings are in perfect accordance with the recently published electron micrographs of isolated extracellular lipid particles from aortic valves 26. Compared with the histological structure of adaptive intimal thickening of human arteries prone to atherosclerotic lesion development,27 the composition of the human aortic valve cusp with the fibrosa suffused with insudated lipoproteins is quite different.…”
Section: Discussionsupporting
confidence: 88%
“…Lp-PLA2 is transported by apoB-containing lipoproteins and is enriched in small, dense LDL and Lp(a) 60 . Lp-PLA2 transforms Ox-PLs into lysophosphatidylcholine (LysoPC), which promotes the loss of mitochondrial membrane potential and apoptosis of VICs 57;61 . In addition, Bouchareb and colleagues recently showed that ectonucleotide pyrophosphatase/phosphodiesterase family member 2 (also called autotaxin), a lysophospholipase D, is likely transported into the aortic valve by Lp(a) and is also secreted by VICs in response to diverse stimuli including tumor necrosis factor alpha (TNF-α) 62 .…”
Section: Mechanisms/pathophysiologymentioning
confidence: 99%
“…9 Also, through nonenzymatic pathways, the oxidation of LDLs generates LPC, 10,11 a highly reactive metabolite with proosteogenic properties and present in mineralized aortic valves. 8,12 Autotaxin (ATX), encoded by the ENPP2 gene, is a lysophospholipase D enzyme that is transported in the blood plasma and secreted by different cell populations. 13 ATX uses LPC as a substrate and produces lysophosphatidic acid, which has potent proinflammatory properties.…”
Section: August 25 2015mentioning
confidence: 99%